L'expérience sociale du quotidien : corps, espace, temps - Haicault, Monique (2000)
Ce livre propose une articulation originale des champs du travail, du privé, des rapports sociaux et de la famille, et constitue une avancée majeure dans le champ de la sociologie des rapports sociaux. Monique Haicault rejette la stérilité de la binarisation traditionnelle, en tenant compte, concrètement et théoriquement, des processus de différenciation sociale de sexe. Son épistémologie « cubique » analyse la triade corps-temps-espace dans le contexte du quotidien et à travers les activités professionnelles, les activités familiales de socialisation, les déplacements urbains et les relations intergénérationnelles. L’utilisation de l’image vidéo donne vie à cette expérience. L’image contribue à montrer comment par leurs comportements, leurs actions, leurs propos et le sens qu’ils donnent à leur expérience, les acteurs sociaux participent de la construction de la société et de sa reproduction dynamique. L’auteure apporte une nouvelle contribution à la socialisation sexuée et à la théorie des rapports sociaux entre sexes et intra-sexe. Elle débouche sur un questionnement qu’il sera désormais difficile de passer sous silence.
Keywords: approches et analyses; corps; discipline; famille; projet charge mentale; rapports sociaux de sexe; sciences humaines; sociologie; thématiques; travail

Something to tell you: the road families travel when a child is gay - Herdt, Gilbert H.; Koff, Bruce (Between men--between women, 2000)
Even now, at the end of the twentieth century, many still have difficulty standing up and saying, "I am the parent of a gay child." Something to Tell You recounts the stories of families whose lives have been touched by the discovery that a child is lesbian or gay—how it affects and influences people's perceptions of their children and even changes the self-image of parents themselves. Focusing on fifty average families—not people seen in clinics or therapy—the authors found a consistent pattern of change: first negative, then positive. Sometimes the news led parents and siblings to form stronger bonds with the child, with each other, and with other relatives and friends. In many cases, their child's partner and partner's family grew to assume an important role in their own lives. In some cases, parents and siblings discovered new meaning in their lives through speaking out or joining PFLAG (Parents, Families, and Friends of Lesbians and Gays) and becoming part of the struggle for lesbian and gay rights. The authors found that families committed to staying together are typically able to overcome the powerful obstacles imposed by society. Something to Tell You also shows the lasting and sometimes tragic consequences for families who falter in the process of integration. Unwilling to accept their child's sexuality, some parents sought to blame each other, and all too often their own relationships unraveled as a result. Others who failed to tell close friends sometimes lost those friends through keeping secrets. Parents who neglected to form bonds with their child's partner fostered climates of alienation that persisted for years. A richly diverse collection of family stories, Something to Tell You is a book that will help break down widespread prejudice and put an end to destructive cultural myths. It affirms families' highest aspirations toward active love for their gay children, showing the steps to take toward new levels of support, solidarity, and love.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; famille; hétérosexisme; patriarcat; premier cycle; relations familiales; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis